A Study On Quality Of Worklife Of Employees At Tvs Automobile Solutions Pvt.Ltd. - K.Murugan; Maran Marimuthu; Peter Sahayaraj; AISHWARYA T.R (Elementary Education Online, 2023)
Quality of work life is the degree to which individuals are able to satisfy their important personal needs while employed by the firm. Quality of work life refers to the level of satisfaction, motivation, involvement and commitment individuals experience with respect to their lives at work. Quality of work life is a process in organizations, which enables its members at all levels to participate actively and effectively in shaping the organization environment, methods, and outcomes. The objective of the study is to help the organization to know the level of satisfaction of the workers and executives at various hierarchical levels, towards the facilities and welfare amenities provided by them and also to find out the challenges and difficulties faced by the management in providing better quality of work life to the employees. Most of the employees covered under my study have not been found to be feeling any stress in their jobs and related working environment. It has been an interesting revelation that there is no employee in TVS Automobiles, is working here just for the sake of the job and most of the employees are not only comfortable with TVS Automobiles, but also feeling proud of being in the company. There should be no communication gap between the team leader and group members. The communication flow must be improved to make it smooth to maintain cordial inter personal relations in the organization. The training and development programs have to be more effectively planned and implemented.